The Effect of Nutrition Education on Knowledge and Practice of Bringing a Balanced Menu to Elementary School Children in Gonting Julu, Huristak District, Padang Lawas Regency in 2021 - Hj. Yusridawati (Institute of Computer Science (IOCS), 2021)
School age (ages 5 to 14 years), is a period of rapid growth and development, increasing physical activity such as playing, exercising or helping parents at work. Good nutritional intake in terms of quantity and quality is needed so that children's growth and development can be optimal. The diet of school-age children tends to be high in snacks and low in fruits and vegetables. The purpose of the study was to determine the Effect of Nutrition Education on Knowledge and Practice of Bringing a Balanced Menu to Elementary School Children in Gonting, Huristak District Padang Lawas Regency in 2021. This type of research is Quasy Experiment with a pre-experimental design with One Group Pretest Posttest design, the population in this study is all elementary school children in grades V and VI as many as 123 people, the sampling technique is purposive sampling, data is taken using a questionnaire and analyzed by paired test t-test The results of the study were that the majority of elementary school children lacked knowledge of 17 people (56.6%), after being given health education about nutrition, 18 people (60.0%), paired t-test results were given p = 0.002 (<0.005), while before given health education, elementary school children still rarely brought rice as many as 20 people (66.6%) and after it was done it increased to often bring rice as many as 24 people (80.0%) the results of the paired t-test test were p = 0.000 (<0.005). Based on the results of the study, it can be concluded that there is an influence of nutritional education on knowledge and practice of bringing a balanced menu to elementary school children in Gonting, Huristak District,